PROMOTION EFFECT ANALYSIS THROUGH DIRECT BONUS IN PACKAGING PRODUCTS, PRODUCT QUALITY, AND BRAND TRUST INTERESTS AGAINST CONSUMERS BUY LIFEBUOY SOAP - RENDI SATIAWAN ELIS PERMANA (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
This research aim was to know influence quality of promotion of direct bonus, quality of product and brand trust to enthusiasm buys consumer at soap product Lifebuoy and factor analysis that was most dominant in influencing enthusiasm to buy consumer at toilet soap Lifebuoy in town Gresik. This research applied sample amounts to 100 mans who taken away from place of expenditure in three districts of town gresik obtained by using technique non probabilty sampling. Analyzer applied is by using doubled linear regression with help of SPSS v.15. examination of hypothesis by using test t and F test, both at level signifikan 5%. Sequential individually from each variable that is very had an effect on was variable Kualitas Produk with regression coefficient 0,336 then variable Brand Trust with regression coefficient 0,337. While variable which its(the influence is lowest is promotion of direct bonus with regression coefficient 0,337. This equation model has calculate F value 19,472 and with level of signifikansi 0,000. Because F calculate bigger than F tables (2,699) and with level of signifikansi which smaller than (0,05). Its showed that independent variable in this research influential joinly to variable dependen that was enthusiasm buys.